(untitled) (Texas Journal of Medical Science, 2023)
Allergies have become increasingly prevalent among children, posing significant health challenges worldwide. This scientific article explores the features and clinical manifestations of the spread of allergies in children. Drawing upon current research and clinical observations, this study examines the various types of allergies commonly encountered in pediatric populations, including food allergies, respiratory allergies, and atopic dermatitis. The article delves into the underlying mechanisms of allergic reactions, risk factors associated with allergy development, and the impact of allergies on children’s physical and psychosocial well-being. Understanding the features and clinical manifestations of allergy spread in children is crucial for early detection, accurate diagnosis, and effective management of allergic conditions